Tracing Italianness: Trans-disciplinary Reflections on Transcultural Italies - Gloudemans, Rachelle (Incontri. Rivista europea di studi italiani, 2021)
Review of: Charles Burdett, Loredana Polezzi and Barbara Spadaro (eds.), Transcultural Italies. Mobility, Memory and Translation, Liverpool, Liverpool University Press, 2020, 368 p., ISBN: 9781789622553, £95.00; ebook: 9781789622706, £95.00.